A module for teaching Arabic to the Malay women’s community in Malaysia: what the experts say - Abdullah, Nawal; Ali, Asem Shehadeh Saleh; Ibrahim, Majdi; Abdul Rashid, Khadijah Khalilah; Nordin, Fitri Nurul Ain; Tg Abdul Rahman, Tg Ainul Farha (Asia Pacific Academy of Science Pte. Ltd., 2023)
The first principle in the process of teaching Arabic for specific purposes is to analyse the needs of students. This process distinguishes between language for general purposes and language for specific purposes which assists students in determining their purpose in learning Arabic, selecting content, and determining teaching methods, assessment of students’ desire. In the present era, it has become the need of the Malay women's community in Malaysia to learn Arabic based on their specialties. Thus, this paper aims to build a unit of educational modules for the Malay women’s community considering their own aspirations and visions. In addition, this paper examines local experts’ views on the proposed module by using convenience sampling. A set of checklists with both open and closed-ended questions were distributed among two experts in the field of Arabic as a second language in Malaysian public universities. Feedback from the experts were collected and analysed.